Against nihilism : Nietzsche meets Dostoyevsky - Stepenberg, Maïa (Black Rose Books, 2018)
"Against Nihilism compares the writings of Nietzsche and Dostoevsky on key topics such as criminality, Christianity and the figure of the Outsider to reveal the urgency and contemporary resonance of their shared struggle against nihilism."--